Generating Real Time Reflections by Ray Tracing Approximate Geometry - Fredriksson, Johan; Scott, Adam (My University, 2016)
Rendering reflections in real time is important for realistic modern games. A common way to provide reflections is by using environment mapping. This method is not an accurate way to calculate reflections and it consumes a lot of memory space. We propose a method of ray tracing approximate geometry in real time. By using approximate geometry it can be kept simple and the size of the bounding volume hierarchy will have a lower memory impact. The ray tracing is performed on the GPU and the bounding volumes are pre built on the CPU using surface area heuristics. The triangle intersection data is pre calculated in order to keep the run time costs low. The method is implemented and tested on the Frostbite game engine.
Keywords: Människa-datorinteraktion (interaktionsdesign); Human Computer Interaction